Effectiveness and safety of acupuncture for post-stroke spasticity: A systematic review and meta-analysis - Xue, Chen; Jiang, Chengzhi; Zhu, Yuanyuan; Liu, Xiaobo; Zhong, Dongling; Li, Yuxi; Zhang, Huiling; Tang, Wenjing; She, Jian; Xie, Cheng; Li, Juan; Feng, Yue; et al. (Frontiers in Neurology, 2022)
Objective This systematic review and meta-analysis aimed to comprehensively evaluate the effectiveness and safety of acupuncture for post-stroke spasticity. Methods Nine electronic databases were searched from their inception to 6 June 2022, to identify randomized-controlled trials (RCTs) that investigated the effectiveness and safety of acupuncture for post-stroke spasticity. Two reviewers independently screened the studies, extracted the data, assessed the risk of bias. The reporting quality of interventions in controlled trials of acupuncture was evaluated using Revised Standards for Reporting Interventions in Clinical Trials of Acupuncture (STRICTA). The RevMan 5.4 and R 4.2.0 software were used for statistical analysis. Results A total of 88 eligible studies were included, involving 6,431 individuals. The pooled data demonstrated that acupuncture combined with conventional rehabilitation (CR) was superior to CR in reducing the Modified Ashworth Scale (MAS) score (standardized mean difference [SMD] = −0.73; 95% CI = −0.83 to −0.63; I2 = 65%; low certainty of evidence). The favorable results were also observed in comparisons of acupuncture vs. CR (SMD = −0.22, 95% CI = −0.36 to −0.07; I2 = 49%; moderate certainty of evidence). Subgroup analysis showed that acupuncture treatment with a frequency of once or twice a day was more effective than CR. In addition, the antispasmodic effect of acupuncture treatment increased with more sessions. Four studies explicitly reported slight acupuncture-related adverse events. Conclusion Acupuncture could be recommended as adjuvant therapy for spasticity after stroke. However, due to the high risk of bias and heterogeneity of the included studies, the effectiveness of acupuncture for post-stroke spasticity remains to be confirmed.